2020
DOI: 10.1007/s00405-020-06067-8
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid disinfection as a potential adjunctive therapy for non-severe COVID-19

Abstract: Purpose SARS-CoV-2 is a new pandemic influenza caused by a coronavirus which main route of transmission is through exhaled droplets that primarily infect the nose and the nasopharynx. The aim of this paper is to evaluate the effect of acetic acid, the active component of vinegar, as a potential disinfectant agent for upper airways. Methods Twenty-nine patients were enrolled and divided into two groups: group 1 (14 patients) was composed of patients treated with off-label hydroxychloroquine and lopinavir/ritona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Prior studies on viral upper respiratory tract infections with hypertonic saline showed decreased viral shedding and reduced patients' infectivity 25 in the already diseased. Others propose other types of medications: in 26 inhalation of acetic acid is suggested being effective in shortening the duration of symptoms. The present study -- besides suggesting the olfactory region as a target for inhibition of the secondary viral infection which endangers the CNS -- provides further support for the effectiveness of such preventive measures, since a diffuse droplet deposition takes place in the nasal fossae, that can be easily reached by washing or by other nasal medications.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on viral upper respiratory tract infections with hypertonic saline showed decreased viral shedding and reduced patients' infectivity 25 in the already diseased. Others propose other types of medications: in 26 inhalation of acetic acid is suggested being effective in shortening the duration of symptoms. The present study -- besides suggesting the olfactory region as a target for inhibition of the secondary viral infection which endangers the CNS -- provides further support for the effectiveness of such preventive measures, since a diffuse droplet deposition takes place in the nasal fossae, that can be easily reached by washing or by other nasal medications.…”
Section: Discussionmentioning
confidence: 99%
“…It destroys the viral envelope and inhibits viral transmission. 13,14 Vinegar is effective in inhibiting the infectivity of virus by lowering the titer by 90% in the nasopharyngeal swab. Also, fumigation of vinegar at low concentration (0.34%) ameliorated the symptoms of mild SARS-CoV-2 infection at a faster rate.…”
Section: Antiviralmentioning
confidence: 99%
“…Also, fumigation of vinegar at low concentration (0.34%) ameliorated the symptoms of mild SARS-CoV-2 infection at a faster rate. 14,15…”
Section: Antiviralmentioning
confidence: 99%
“…Based on ancient medical tradition [6], in order to mitigate virus replication and its consequences in the upper respiratory tract mucosa, including acute anosmia (a frequent early symptom of SARS-CoV-2 infection [7]), fumigation of vinegar diluted in boiling water at a concentration of 0.34% for 15 min has been adopted as an empirical practice in COVID-19 patients. Indeed, improvement of symptoms such as coughing and fever was observed in >90% of individuals [8].…”
Section: Introductionmentioning
confidence: 98%